2020
DOI: 10.1371/journal.pone.0241106
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual knowledge, sociocultural restrictions, and barriers to menstrual hygiene management in Ghana: Evidence from a multi-method survey among adolescent schoolgirls and schoolboys

Abstract: On a daily basis, schoolgirls in low and middle-income countries discover blood on their clothing for the first time in school environments without toilets, water, or a supportive teacher, mentor, or role model to help them understand the changes happening in their bodies. This study aimed to examine the menstrual knowledge, sociocultural restrictions, and barriers to menstrual hygiene management in school environment among adolescent schoolgirls in a rural community. We collected quantitative data from 250 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 18 publications
4
91
0
7
Order By: Relevance
“…Lack of sanitary pads has also been widely reported to be a major contributory factor to school absenteeism among girls in their menstrual period [7,10,14,15]. Other documented factors such as cultural restrictions, age of girls and mother's education are said to play an influence on menstruation-related school absenteeism [7,16]. Selfreported factors such as menstrual pain, fear of staining clothing and fear of being teased at school have also been reported to be associated with school absenteeism [8,9,17].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of sanitary pads has also been widely reported to be a major contributory factor to school absenteeism among girls in their menstrual period [7,10,14,15]. Other documented factors such as cultural restrictions, age of girls and mother's education are said to play an influence on menstruation-related school absenteeism [7,16]. Selfreported factors such as menstrual pain, fear of staining clothing and fear of being teased at school have also been reported to be associated with school absenteeism [8,9,17].…”
Section: Introductionmentioning
confidence: 99%
“…The need for this secrecy can perhaps also be linked to cultural perceptions and influences. Mohamed and Larsen-Reindorf (2020) reports that in a study conducted in Ghana it was found that men and boys play an influential role in supporting girls in their menstrual hygiene management and menstruation experience. It is deemed important that an understanding of menstruation and the challenges associated with it is made known to adolescent boys.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, (14,15,16) found that, in Ghana, not only did the family's socio-economic status played a major role in access to sanitary pads for girls, but also impacted on their level of knowledge on menstrual health. The aforementioned studies also indicated that inappropriate school WASH facilities, lack of regular supply of water, and socio-cultural barriers, such as, myths about menstruation, and lack of open discussions on menstrual issues, created menstrual barriers for girls.…”
Section: Overview Of Menstrual Health Management Among Schoolgirlsmentioning
confidence: 99%